Heavy Chains of Inter Alpha Inhibitor (IαI) Inhibit the Human Complement System at Early Stages of the Cascade - Okroj, Marcin (American Society for Biochemistry and Molecular Biology, 2012)
Inter alpha inhibitor (IαI) is an abundant serum protein consisting of three polypeptides: two heavy chains (HC1 and HC2) and bikunin, a broad-specificity Kunitz-type proteinase inhibitor. The complex is covalently held together by chondroitin sulfate but during inflammation IαI may interact with TNF-stimulated gene 6 protein (TSG-6), which supports transesterification of heavy chains to hyaluronan. Recently, IαI was shown to inhibit mouse complement in vivo and to protect from complement-mediated lung injury but the mechanism of such activity was not elucidated. Using human serum depleted from IαI, we found that IαI is not an essential human complement inhibitor as was reported for mice and that such serum has unaltered hemolytic activity. However, purified human IαI inhibited classical, lectin and alternative complement pathways in vitro when added in excess to human serum. The inhibitory activity was dependent on heavy chains but not bikunin and detected at the level of initiating molecules (MBL, properdin) in the lectin/alternative pathways or C4b in the classical pathway. Furthermore, IαI affected formation and assembly of the C1 complex and prevented assembly of the classical pathway C3-convertase. Presence and putative interactions with TSG-6 did not affect the ability of IαI to inhibit complement thus implicating IαI as a potentially important complement inhibitor once enriched onto hyaluronan moieties in the course of local inflammatory processes. In support of this, we found a correlation between IαI/HC-containing proteins and hemolytic activity of synovial fluid from patients suffering from rheumatoid arthritis.